Assessing DX through the correlation between affectivity and self-assessed productivity in a public institution - Lopes, Fabian Oliveira; Oran, Ana Carolina; Gadelha, Bruno (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2022)
The human aspects of software development have received attention in recent years, especially with studies related to Developer Experience (DX). Activities related to development have a cognitive processing character. There is a link between affectivity (emotions, moods and feelings), cognitive processing and individual productivity. The objective of this study is to evaluate the DX in the development teams in the public service, in the environment of the Municipality. To achieve this objective, we used the correlation between the affective dimensions of valence, arousal and dominance with self-assessed productivity (sPR). This correlation measures the impact of affectivity effects on the productivity of development activities. The study was carried out with 11 municipal public service software development professionals in their daily activities through the use of interviews, questionnaires and the Self-Assessment Manikin (SAM) technique. The results demonstrate the importance of DX assessment in individual productivity, valuing human aspects and their influence on software development.